CIAT research on improving livelihoods of smallholder coffee producers in Nicaragua - Blundo Canto, Genowefa M.; Pérez, L.; Zuluaga Gonzalez, V.; Läderach, Peter R.D. (2015)
The results of CIAT’s studies have provided the scientific basis for the collaborative design and implementation of a series of CRS-led projects, also providing recommendations and lessons learned from each project into the proposal and implementation of the next. In this study, we specifically evaluate the short-term impacts of a project for the improvement of smallholder coffee producers’ livelihoods carried out in Nicaragua by CRS with collaboration from CIAT between 2011 and 2014. The project, called “BRIDGES: Bridges from Scarcity to Sufficiency’’ was the latest in a chain of interventions in Nicaragua led by CRS, and to which CIAT has contributed since 2009. Based on data collected in 2014 to help design and to assign treatment and control groups for a new CRS project (Resilience to Rust), which include information on BRIDGES participants, our findings show that participation in the BRIDGES project has increased months of adequate food provision (MAHFP) for project beneficiaries by 0.3 months, by increasing economic access to food via increased production. Participation in BRIDGES appears associated with an increase in bean yields, of about 230 kg per hectare, and in an increase of almost one income source, however these results are sensitive to different model specifications. Finally, participations in BRIDGES appears associated with a 6% reduction in household dependency from coffee income.